Hubungan status gingiva dengan kebiasaan menyirih pada masyarakat di Kecamatan Manganitu - Hontong, Cheny; Mintjelungan, Christy N.; Zuliari, Kustina (e-GiGi, 2016)
Abstract: Oral health is very important for every individual. Gingivitis is an inflammation of the gingiva caused by the interaction of microorganisms in plaques and bad habits inter alia the habit of chewing betel. This study was aimed to determine the relationship of gingival status and chewing habits based on the duration of betel chewing and chewing frequencies per day among Manganitu district community. This was a descriptive-analytical study with a cross-sectional design. Samples were taken by using purposive sampling. There were 39 respondents as samples. Clinical data of the gingival status was measured by using gingival index (GI) of Loe and Sillnes. The results of chi-square analysis showed a significant correlation between the gingival status and the betel chewing habit based on the duration of betel chewing habit (p = 0.000) and the frequency of betel chewing per day (p = 0.001). Conclusion: Gingival status of Manganitu district community who had betel chewing habit was classified in the severe category.Keywords: Status gingiva, chewing habits, Manganitu districts.Â Abstrak: Kesehatan gigi dan mulut sangat penting bagi setiap individu. Gingivitis merupakan inflamasi pada gingiva yang disebabkan oleh interaksi mikroorganisme pada plak dan kebiasaan buruk, salah satunya ialah kebiasaan menyirih. Penelitian ini bertujuan untuk mengetahui hubungan status gingiva dengan kebiasaan menyirih berdasarkan lama menyirih dan frekuensi menyirih perhari pada masyarakat kecamatan Manganitu. Jenis penelitian ialah deskriptif-analitik dengan desain potong lintang. Sampel diperoleh dengan metode purposive sampling sebanyak 39 responden. Data klinis tentang status gingiva diukur menggunakan gingival index (GI) menurut Loe dan Sillnes. Berdasarkan hasil uji analisis chi-square terdapat hubungan bermakna antara status gingiva dengan kebiasaan menyirih berdasarkan lama menyirih (p=0,000) dan frekuensi menyirih (p=0,001). Simpulan: Status gingiva masyarakat kecamatan Manganitu yang memiliki kebiasaan menyirih tergolong dalam kategori berat. Kata kunci: status gingiva, kebiasaan menyirih